OP0186 Analysis of Uveitis Events in the BIOLOGICS in Pediatric Rheumatology (BIKER)-Registry. (10th June 2014) - Horneff, G.; Foeldvari, I.; Minden, K.; Tenbrock, K.; Huppertz, H.I.; Becker, I.
Abstract : Background: Uveitis is one of the major extraarticular manifestations of JIA. Open studies demonstrate efficacy of Adalimumab (ADA) and Infliximab. It remains unclear if uveitis can occur as an adverse drug reaction, especially in pts. exposed to Etanercept (ETA). Methods: The BIKER registry data base was used for analysis. Patient's history of uveitis, JIA category, the first occurrence of uveitis and exposure to Methotrexate (MTX), ETA, ADA and steroids were searched for. The number of first uveitis events occurring in each treatment category, the no. of exposed patients and exposure time until event were calculated. Results: Of 3467 pts, 1700 were exposed to ETA, 364 to ADA and 1403 to MTX only. 335 pts (9.4%) had a history of uveitis before. In 75 pts (2.2%) uveitis was reported as an adverse event. Pts. with a known history of uveitis were more likely to have a new uveitis event (n=22; 6.8%; OR 2.9 [1.5-5.5]; p<0.001) than patients without. In 16 pts the first occurrence of uveitis was reported: 11 in the MTX cohort, 5 in the biologics cohort, 2 with ETA monotherapy and 3 with ETA&MTX. Uveitis events occurred more frequently in pts. with ext.oligoJIA (OR 2.4[1.4-3.9]; p=0, 0005) and less likely systemic JIA (OR 0.22[0, 03-1, 59; p=0.1) or rheumatoid factor pos. polyJIA (OR 0.19[0.03-1.34]; p=0.06) and more likely had ANA (OR 2.5 [1.5-4.1]; p<0.0003). Moreover, pts with an uveitis event were younger (4.6±4.1 years vs. 7.6±4.6 years; p<0.0001). Pts. with a history of uveitis before treatment with a biologic were more likely to receive ADA than ETA (OR 2.90 [2.06-4.08]; p<0.0001). To analyze the influence of drug treatment on the occurrence of a first uveitis flare pts' treatments were categorised (table). Compared to the control group (MTX only) OR was significantly higher in pts receiving ETA monotherapy. It was not increased in combination with MTX. There were more uveitis events in pts on ADA±MTX in combination. Univariate analysis revealed that treatment with corticosteroids seems not to protect from uveitis, while MTX did. Pts. on ADA had significantly higher rates, while pts on ETA did not. Conclusions: Risk factors for uveitis as an adverse event were history of uveitis and ETA mono therapy. MTX treatment did reduce the likelihood of uveitis whereas corticosteroids had no such effect. Few pts developed first uveitis when exposed to ETA with a rate comparable to the control group. Disclosure of Interest: G. Horneff Grant/research support: Abbvie, Pfizer, Roche/Chugai, I. Foeldvari: None declared, K. Minden: None declared, K. Tenbrock: None declared, H. Huppertz: None declared, I. Becker: None declared DOI: 10.1136/annrheumdis-2014-eular.2702